Prinsip Pengelolaan Keuangan Pribadi Berdasarkan Etika Kristen Bagi Mahasiswa - Ribka Windha Agustien; Wahyu Wijiati (STT IKSM SANTOSA ASIH, 2026)
This research was conducted with the aim of providing insights into the principles of financial management based on Christian ethics for college students. Since the beginning, human life has always been intertwined with the use of money, especially in today’s era of digitalization. However, money—referring here to unhealthy financial management often tends to lead a person to sin, particularly for Christian college students. In fact, many experts in the field of economics have contributed their insights on the subject of wise money management. Nevertheless, it is important to realize that these principles do not originate from the truth of God’s Word. Therefore, as Christians, especially as Christian college students, it is essential to understand the principles of healthy personal financial management based on God’s Word in the teachings of Christian ethics. The method used by the researcher is a qualitative research method with a literature review approach. Several previous studies have examined the areas of financial management and Christian ethics. However, to date, existing studies have focused more on church financial management and Christian ethics in decision-making and youth relationships. Therefore, the researcher offers a different perspective in this study by discussing the principles of personal financial management based on Christian ethics for college students.